The Contribution of Managers to Organizational Success: Evidence from German Soccer - Sandra Hentschel; Gerd Muehlheusser; Dirk Sliwka (Institute for the Study of Labor (IZA), 2014)
We study the impact of managers on the success of professional soccer teams using data from the German "Bundesliga". We evaluate the performance impact of individual managers by estimating regression models that include both team and manager fixed effects, where we are exploiting the high turnover of managers between teams to disentangle the managers' contributions. We find that teams employing a manager at the 75% ability percentile gain on average 0:25 points per game more than those employing a manager at the 25% ability percentile, which corresponds to a sizeable difference of 18% of the average number of points awarded per game. Moreover, estimated abilities have significant predictive power for future performance.
Keywords: J24; J44; J63; 330; managerial skills; human capital; empirical; fixed effects; professional sports